2021
DOI: 10.1101/2021.04.29.21256002
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 sculpts the immune system to induce sustained virus-specific naïve-like and memory B cell responses

Abstract: SARS-CoV-2 infection induces virus-reactive memory B cells expressing unmutated antibodies, which hints at their emergence from naïve B cells. Yet, the dynamics of virus-specific naïve B cells and their impact on immunity and immunopathology remain unclear. Here, we longitudinally studied moderate to severe COVID-19 patients to dissect SARS-CoV-2-specific B cell responses overtime. We found a broad virus-specific antibody response during acute infection, which evolved into an IgG1-dominated response during con… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 63 publications
5
10
0
Order By: Relevance
“…Following primary immunization, individuals with preexisting immunity showed increased titers of all antibodies except IgG3 against WT and VOCs, when compared to SARS-CoV-2 naïve subjects. Our data were consistent with recent studies that reported the presence of pre-existing SARS-CoV-2-specific and cross-variant specific-memory B cells in COVID-19 recovered subjects (16,17,19,20,35). In line with our results, a recent report showed a strong correlation between the frequency of SARS-CoV-2-specific memory B cells at baseline and the antibody concentrations following vaccination (6).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Following primary immunization, individuals with preexisting immunity showed increased titers of all antibodies except IgG3 against WT and VOCs, when compared to SARS-CoV-2 naïve subjects. Our data were consistent with recent studies that reported the presence of pre-existing SARS-CoV-2-specific and cross-variant specific-memory B cells in COVID-19 recovered subjects (16,17,19,20,35). In line with our results, a recent report showed a strong correlation between the frequency of SARS-CoV-2-specific memory B cells at baseline and the antibody concentrations following vaccination (6).…”
Section: Discussionsupporting
confidence: 93%
“…Following the first vaccine dose, COVID-19 recovered individuals show significantly higher Sand RBD-specific IgG titers, superior serum neutralization activity (7,(12)(13)(14), and increased S protein-specific memory T and B cell responses than naïve individuals (4)(5)(6)15). This enhanced response is consistent with the persistence of humoral and cellular immunity against SARS-CoV-2 in convalescent individuals, as previously reported (16)(17)(18)(19)(20).…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…Following the first vaccine dose, COVID-19 recovered individuals show significantly higher S-and RBD-specific IgG titers, superior serum neutralization activity 7,1113 , even against SARS-CoV-2 variants 8,14,15 , and increased S protein-specific memory T and B cell responses than naïve individuals 4–6,14 . This enhanced response is consistent with the persistence of humoral and cellular immunity against SARS-CoV-2 in convalescent individuals, as previously reported 1620 . Because a recall immunization does not seem to provide any quantitative benefit in subjects with pre-existing immunity to SARS-CoV-2 6,7,13 , it has been proposed that COVID-19 recovered people may only require a single vaccine dose to achieve optimal immune protection 6,7,13 .…”
Section: Introductionsupporting
confidence: 91%